ANALISIS PERBEDAAN ABNORMAL RETURN DAN TRADING VOLUME ACTIVITY SEBELUM DAN SESUDAH PERISTIWA PENETAPAN UNDANG-UNDANG TAX AMNESTY - I Komang Wisnu Wardhana; Hermanto Hermanto; I Nyoman Nugraha AP (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2021)
The purpose of this study was to determine the difference in the average abnormal return and trading volume activity before and after the enactment of the tax amnesty law on the LQ-45 index. The type of data used in this study is secondary data with data collection techniques using the documentation method. Determination of the sample in this study using purposive sampling method with certain criteria so as to obtain 45 samples. The analytical technique used in this research is paired sample t-test with an observation period of 10 days. The results of this study indicate that: (1) There is no difference in the average abnormal return before and after the enactment of the tax amnesty law. (2) There is no difference in the average trading volume activity before and after the enactment of the tax amnesty law.